Improving our understanding of the use of traditional complementary/alternative medicine in children with cancer. Issue 9 (29th December 2014) - Ladas, Elena J.; Lin, Meiko; Antillion, Federico; Rivas, Silvia; Chantada, Guillermo; Cacciavillano, Walter; Ortiz, Roberta; Stein, Katja; Castillo, Luis; Rocha, Valeria; Fu, Ligia; Rodriquez, Hilze; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Children with cancer in high‐income and low‐income countries often use traditional complementary/alternative medicine (TCAM). With efforts by the World Health Organization and international twinning programs improving access to conventional care for patients with childhood cancer, understanding the global use of TCAM is important because reliance on TCAM may affect time to presentation, adherence, and abandonment of care. In the current study, the authors describe the process and validation of an international survey documenting the use of TCAM among children with cancer. METHODS The survey was designed to collect information on TCAM use and associated factors through both open‐ended and close‐ended questions. During the period between June 2012 and December 2013, the survey was administered to 300 children and adolescents (or their parents) who were undergoing treatment for cancer at a collaborating institution located in Mexico, Uruguay, and Nicaragua. RESULTS For the majority of constructs, the survey demonstrated strong test‐retest reliability as evidenced by an intraclass correlation of at least ≥0.79 in each of the participating countries. The survey demonstrated good internal consistency and reliability across countries (α range from. 77 to. 85 for the belief scale; and an α range from. 60 to. 86 for the cause scale) and convergent validity between TCAM beliefs and behavior constructs (adjusted correlation range, 0.35‐0.60). CONCLUSIONS The results of the current study demonstrate the successful development of a cross‐cultural survey that produced results that were reliable and valid. These findings will aid investigators in providing guidelines concerning TCAM, support the development of education and research priorities, and identify variables associated with TCAM that are region‐specific. Cancer 2015;121:1492–1498. © 2014 American Cancer Society.